General public knowledge and perception towards herbal beverages in Kuantan, Malaysia - Al-Shami, Abdul Kareem; Elkalmi, Ramadan Mohamed Mahmod; Jamshed, Shazia Qasim; Awadh, Ammar Ihsan Jawad; Elsayed, Tarek Mohamed Ali; Al-lela, Omer Qutaiba; Nazar, Nor Ilyani; Shamsudin, Siti Hadijah (2014)
Bachground Herbal beverages are already well-known to people nowadays. They can be considered as nutritional drinks with the addition of some herbs to the beverage. The current study is aimed to evaluate General Public Knowledge and Perception towards Herbal Beverages in Kuantan, Malaysia.